Salinity Tolerance of Mungbean Genotypes at Seedling Stage - Ratri Tri Hapsari; Trustinah Trustinah (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Salinity is a major abiotic stress limiting mungbean production worldwide including Indonesia. Since mungbean plant is very sensitive to salt condition, selection of salinity tolerant genotypes becomes important for mungbean improvement. The objective of this study was to evaluate the tolerance of eight mungbean genotypes to salinity at seedling stage under different levels. The experiment was arranged in a randomized complete block design with two factors (mungbean genotypes and salinity levels) and triplicates. Observation variables were germination percentage, vigor index, germination rate, hypocotyls length, epicotyls length, root length, number of root, seedling fresh weight, and seedling dry weight. The result showed that increasing level of salinity concentration inhibited the speed of germination, germination percentage, vigor index, normal seedling fresh weight, and number of lateral roots. Murai and Vima 1 were identified as tolerant genotypes, while Vima-2 and MLGV 0180 were identified as salinity sensitive genotypes at seedling stage. Currently, mungbean varieties with special characters, such as saline-tolerant is not yet available. The availability of saline-tolerant variety of mungbean is a cheaper and easier technology for farmers to anticipate the expansion of the saline area. The tolerant genotypes may be further tested at the later stage to obtain promising genotype tolerant to salinity that effectively assist mungbean breeding program.